A new record species Rothmannia wittii (Craib) Bremek. (Rubiaceae) for the flora of Vietnam - Quang, Bui Hong; Cuong, Nguyen The (Academia Journal of Biology, 2015)
Rothmannia wittii (Craib) Bremek. a species of Rubiaceae, was found for the first time for Vietnam. The present paper provides the species description, line drawing and color illustration of R. wittii, species. A key to species and distribution map of five species of Rotthmannia in Vietnam. Is provided. The diagnostic characters of R. daweishanensis and R. wittii are also given.